Spatial features of lifecell mobile network in the western part of Ukraine - Puhach, Serhii; Fedoniuk, Mykola; Korol, Pavlo; Dobrovolska, Nataliia (Human Geography Journal, 2022)
Today, social communications and business are increasingly moving towards the mobile Internet. However, the information revolution also has a downside, namely the need to be always in touch and on-line. Nowadays, business is no longer limited to the office, and social communications are no longer limited to certain locations. It is important to have good mobile coverage, whether you are on the move or not. As a result, entire areas become more "suitable" for living and working than others. This measurement is based on only one indicator – the availability of a mobile network. The smartphone has become an access point to the global Internet network. In 2022, the number of unique mobile Internet users was 5 billion, which is more than 60% of the world's population.Geographical studies of mobile communication networks in Ukraine are not widespread. The available publications are mostly descriptive in nature. They consider Ukraine as whole unit without any intra-regional differences. Several scientific studies on the Kyivstar mobile network have a clearly expressed territorial aspect. At the same time, other networks - primarily Vodafone Ukraine and Lifecell - remain little studied. The purpose of the study is to determine the spatial features of the Lifecell mobile network in the western part of Ukraine, and the main task is to analyse the coverage indicators of the Lifecell mobile communication network at the local level in the western part of Ukraine based on open data.The Lifecell mobile network in the western part of Ukraine creates the following spatial patterns. Lifecell is the third largest mobile operator in Western Ukraine. In terms of network volume, it is behind its main competitors Kyivstar and Vodafobe. Its 3G mobile network is larger than its 4G network. Lifecell's network coverage primarily covers large cities and their surrounding areas. In rural areas, the network is poorly developed. In terms of sub-regions, Lviv oblast and Prykarpattia have the best coverage, while the Ukrainian Carpathians (except for the territories of Lviv oblast), the eastern part of Volyn Polissya, and the southern and eastern parts of Ternopil oblast have the worst coverage of the Lifecell network.